ICAT-EGVE 2018 Posters and Demos Proceedings - (:unkn) unknown (My University, 2026)
Huang, T., Otsuki, M., Servières, M., Dey, A., Sugiura, Y., Banakou, D., & Michael-Grigoriou, D. (Eds.). (2018). ICAT-EGVE 2018 – International Conference on Artificial Reality and Telexistence and Eurographics Symposium on Virtual Environments – Posters and Demos. The Eurographics Association.